AN EVALUATION OF THE EFFECT OF LARVICIDING OPERATIONS IN RURAL AREAS NEAR ABADAN, IRAN - E. Javadian; M.A. Acheson (Tehran University of Medical Sciences, 1974)
Anti-Larval measures were carried out in and around the city of Abadan in conjunction with residual spraying against the only malaria vector of the area.  A.stephensi which has developed resistance to both DDT and Dieldrin. There is evidence that larviciding is a valuable measure for reducing the A. stephensi population when used as a supplement to Malathion, which has relatively short residual effect.